Reversine ameliorates hallmarks of cellular senescence in human skeletal myoblasts via reactivation of autophagy. Issue 3 (10th January 2023) - Rajabian, Nika; Choudhury, Debanik; Ikhapoh, Izuagie; Saha, Shilpashree; Kalyankar, Aishwarya S.; Mehrotra, Pihu; Shahini, Aref; Breed, Kendall; Andreadis, Stelios T.
Abstract: Cellular senescence leads to the depletion of myogenic progenitors and decreased regenerative capacity. We show that the small molecule 2, 6‐disubstituted purine, reversine, can improve some well‐known hallmarks of cellular aging in senescent myoblast cells. Reversine reactivated autophagy and insulin signaling pathway via upregulation of Adenosine Monophosphate‐activated protein kinase (AMPK) and Akt2, restoring insulin sensitivity and glucose uptake in senescent cells. Reversine also restored the loss of connectivity of glycolysis to the TCA cycle, thus restoring dysfunctional mitochondria and the impaired myogenic differentiation potential of senescent myoblasts. Altogether, our data suggest that cellular senescence can be reversed by treatment with a single small molecule without employing genetic reprogramming technologies. Abstract : Our results suggest that short‐term treatment of senescent myoblasts with reversine could restore insulin resistance, enhance glucose metabolism and oxidative phosphorylation, likely via reactivation of autophagy. Restoring DNA damage and the state of heterochromatin preceded restoration of proliferation, SA‐β‐Gal expression, and cell size in reversine‐treated cells, ultimately restoring the differentiation ability of myoblasts to form myofibers. Therefore, reversine may have the potential to be used as a novel, anti‐aging treatment, without the tumorigenic complications of genetic reprogramming technologies.